Simple Additive Weighting sebagai Metode Pendukung Keputusan terhadap Sistem Customer Satisfaction - Ayu Rahmadani; Dewi Maharani; Sahren Sahren (Jurnal Pendidikan Informatika (EDUMATIC), 2022)
Nazwa drugstore is one of the stores that still use manual methods to recognize complaints about service for customers who come to the store, so it is felt to be less effective. Therefore, it is necessary to have a system to measure customer satisfaction in the store quickly and accurately. To build this system, we apply the Simple Additive Weighting (SAW) method to determine user satisfaction. The model used to build this system is the System Development Life Cycle (SDLC) with stages of analysis, design, implementation, and trial. At the analysis stage, we used interview and observation methods to collect data. Our design phase consists of a use case, a system interface, and a diagram class. Testing this system uses a black box to see if all the components of the system are working properly. Our findings are to produce a decision support system for customer satisfaction using the SAW method. In addition, this system also has a user-friendly and responsible interface, so this system is easy to use. The results of the black box test show that all components in this system are already functioning properly.